The Greek Theatre in the United States from the End of the 19th Century to the 21st Century - Diakoumopoulou, Katerina (Études helléniques / Hellenic Studies, 2008)
This article covers the theatre activity of the Greek immigrants in the USA from the end of the nineteenth century until today. It outlines the history of the many theatre groups which had appeared in the American Greek communities by the end of the nineteenth century and thrived until the marked decline in the second decade of the twentieth century precipitated by the enlistment of many young Greek immigrants for the Balkan Wars. The impressive development which followed from 1920 to 1940, and then after the Second World War, is examined with focus on a variety of aspects, such as the many companies (amateur and professional) and their repertories, themes, trends, problems, political influences, social issues, etc., necessary for an understanding of the role and impact which the Greek theatre has had to the present time. Two particular trends noted since World War II are that the Greek American playwrights compose their works mainly in English and that many second generation Greek Americans participate in Greek theatre groups, while a number of first generation actors with long service in the theatre have become professionals.